New species and records of Anchocerus Fauvel in China (Coleoptera: Staphylinidae: Staphylininae) - Lin, Xiao-Bin; Hu, Jia-Yao (Zootaxa, 2021)
Two species of Anchocerus Fauvel are reported from China, one of them described as new: A. wenxuani Lin & Hu, sp. n. (Guangxi). Anchocerus giganteus Hu, Li & Zhao, 2010 is newly recorded from Shanghai, Jiangxi, Guangxi and Guangdong. A map showing the distribution of all Chinese species is provided.